Research Results on the Factors Affecting Precision Sowing of Onion Seed - Makhkamov G. U.; Mamadjonov E. (American Journal of Biology and Natural Sciences, 2024)
This article presents the results of research on seed sowing. It also presents an analysis of the literature on the modes of movement of the sowing machine, the seed box, the movement of seeds, and the modes of seed landing in the cells.